The Effect of Reading, Questioning, and Answering (RQA) Learning Model on Students' Critical Thinking Ability in Science Material at SD Negeri 15 Sorong City - Safitri, Riska Dwi; Afifi, Erwinestri Hanidar Nur; Shaharani, Aishya (Journal of Asian Primary Education (JoAPE), 2024)
This research was motivated by problems in the world of education including curriculum changes, learning quality, and how educators carry out the process and application of learning models to improve critical thinking skills in students. Observations show that teaching carried out by educators is still teacher centred and the lecture method is more often used in delivering material. The Reading, Questioning, and Answering (RQA) learning model can assist students in developing their critical thinking skills through the assigned reading. RQA allows students to study the material, look for important points in the form of questions and look for answers to important issues from different sources. Critical thinking is very important for students to have since elementary school. Critical thinking skills provide logical and creative reasoning in thinking and solving problems. This research was conducted in science subjects at SD Negeri 15 Sorong City. The sample size of this study was 40 students divided into two classes: IV, A and IV B. This research is a quantitative approach with the type of research Quasi Experiment Control Group Pretest Post-test design. The results of the analysis show that the data is normally distributed and homogeneous and the results of the calculation of t-Sig (2 tailed) of 0.001 <0.05, it can be concluded that H0 is rejected and H1 is accepted, which means that there is a difference between the critical thinking skills of students in the control class and the critical thinking skills of students in the experimental class who are given treatment using the RQA model.